Peran Kemampuan Komunikasi Interpersonal Pendidik Dalam Menumbuhkan Self-Efficacy - Muhammad Fadali Amar (Aafiyah: Jurnal Multidisiplin Ilmu, 2024)
This study discusses the role of educators' interpersonal communication skills in cultivating students' self-efficacy at SMP Al-Furqon Jambesari, Bondowoso, This study shows educators who have good interpersonal communication skills will be inspirational for students, educators will be their drivers to be active, committed and have a high interest in learning, educators who are able to communicate interactively create a positive and inclusive learning environment, This study used descriptive qualitative. Although the role of educators' interpersonal communication in cultivating self-efficacy is going well, there are still some obstacles, some students still need guidance and direction in developing self-efficacy, lack of confidence in themselves can hinder the effectiveness of learning, therefore educators must provide constitutive support and feedback to students so that they are confident in facing challenges. The integration of educators' interpersonal skills towards students' self-efficacy is done by providing direct emotional support, recognizing students' efforts in learning and rewarding their achievements. The results showed that educators who are inspirational and have good interpersonal communication can help students overcome insecurity and increase confidence in their abilities. This research emphasizes the importance of the role of educators as inspiration, the role of educators as central students in growing students, and integrating educators' interpersonal communication towards self-efficacy. It is hoped that the results of this research can be a reference in improving the quality of learning and student development in schools.